Crew of whaling schooner A.T. Gifford putting ash on the ice, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1907)
Crew members are engaged in spreading ash on the ice in front of the whaling schooner A.T. Gifford, in winter quarters in Hudson Bay, Canada, ca. 1907-1912. The vessel can be seen in the background. The men are identified as spreading ash in a path leading from the schooner out of the harbor. Environment Livelihood Infrastructure Title supplied by cataloger. Information from original envelope identifies this as # 35B. The ashes were intended to work down through the ice, making it easier to get the vessel out of the harbor as the weather warmed. The schooner A.T. Gifford was built in 1883 at Essex, Massachusetts. George Comer was her master during one of his Arctic voyages in which he mapped areas in the Hudson Bay area. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.